Efficiency evaluation and comparison between non-banking financial institutions and commercial banks of Bangladesh - Fahim, Fariduzzaman (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.